TATA CARA PELAPORAN PAJAK TERHUTANG SURAT PEMBERITAHUAN MASA TERHADAP PAJAK PERTAMBAHAN NILAI PADA CV BINA PRATAMA REKAYASA - Nasution, Nina Andriany; Fitriani, Annisa (JURNAL PERPAJAKAN, 2025)
Value Added Tax Return Notice is used by corporate taxpayers to calculate the amount of tax that must be paid when subject to Taxable Goods (BKP) or Taxable Services (JKP) that must be reported. In addition to reporting payments or returning tax returns, Value Added Tax refunds can also be used to report assets and liabilities and pay taxes to buyers or collectors. Tax Notification Periods are usually reported every month, even if the balance does not change or the value of the rupiah in the relevant tax period is zero (0). The due date of the report is at the end of the following month, which is the 30th or 31st month after the tax period. Except for certain conditions described in Ministry of Finance regulations PER-80 / PMK.03 / 2010, the due date is not the end of the following month after the end of the relevant control period. If it is too late to report the VAT notification, a fine of Rp. 500,000 (KUP Article 7 (1))